2010
DOI: 10.1093/jxb/erq061
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence development in petunia: through the maze of botanical terminology

Abstract: Flowering plants have developed many ways to arrange their flowers. A flower-bearing branch or system of branches is called an inflorescence. The number of flowers that an inflorescence contains ranges from a single flower to endless flower-clusters. Over the past centuries, botanists have classified inflorescences based on their morphology, which has led to an unfortunate maze of complex botanical terminology. With the rise of molecular developmental biology, research has become increasingly focused on how in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 45 publications
0
41
1
Order By: Relevance
“…Many plant families contain species with inflorescences described as racemes and cymes (Watson and Dalwitz, 2007), suggesting that these structures evolved multiple times independently. However, the details are hard to reconstruct with certainty because inflorescence architecture is (often) misclassified for a variety of reasons (Castel et al, 2010). In addition, assessing when the regulatory differences in pDOT and pUFO arose during evolution requires data on the regulation of DOT/UFO homologs in many more (related) species than currently available.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many plant families contain species with inflorescences described as racemes and cymes (Watson and Dalwitz, 2007), suggesting that these structures evolved multiple times independently. However, the details are hard to reconstruct with certainty because inflorescence architecture is (often) misclassified for a variety of reasons (Castel et al, 2010). In addition, assessing when the regulatory differences in pDOT and pUFO arose during evolution requires data on the regulation of DOT/UFO homologs in many more (related) species than currently available.…”
Section: Discussionmentioning
confidence: 99%
“…The slightly delayed expression of endogenous ALF in SIMs compared with the apical FM (Souer et al, 1998) was not observed with the limited resolution of GUS assays. This is not surprising because (i) the SIM emerges as a very small region between the bract and the apical FM, which both express ALF, and because (ii) ALF expression in the SIM is only briefly delayed (Souer et al, 1998;Castel et al, 2010). In Arabidopsis inflorescences, however, expression of pLFY: GUS and pALF:GUS was restricted to lateral FMs (Fig.…”
Section: Promoter Regions Sufficient For Correct Spatio-temporal Exprmentioning
confidence: 93%
See 3 more Smart Citations